The Role of Information and Communication Technology in Interactive Learning - Elmi, Hafiz; Ambiyar, Ambiyar; Huda, Yasdinul; Novaliendry, Dony (Jurnal SAINTIKOM (Jurnal Sains Manajemen Informatika dan Komputer), 2024)
This article is the result of an in-depth literature review on the role of Information and Communication Technology (ICT) in the context of interactive learning. Education has undergone a significant transformation with the adoption of ICT, transforming the traditional way of learning into a more dynamic and participatory learning experience. The purpose of this literature review is to analyse the positive impact of ICT in shaping interactive learning environments, explore the use of multimedia in the learning process, and identify the challenges and opportunities associated with the application of ICT in education. This literature review describes the transformation of learning through ICT, explaining the paradigm shift from conventional approaches to more adaptive and collaborative interactive learning. The results of this literature review illustrate how important the role of ICT is in shaping the future of education that is more interactive, inclusive and relevant to the demands of the times. Through collaboration between educational institutions, government, and the technology industry, as well as a careful pedagogical approach, ICT can be a catalyst to optimise the learning process and empower students to face the complexities of the modern world.